Efeito de um protocolo de treinamento concorrente sobre fatores de risco para o acúmulo de gordura hepática de adolescentes obesos - Monteiro, Paula A. [UNESP]; Antunes, Barbara M. M. [UNESP]; Silveira, Loreana S. [UNESP]; Fernandes, Romulo A. [UNESP]; Freitas Jr., Ismael F. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Study Design: Prospective study Objective: To evaluate the effect of a protocol of concurrent training lasting 16 weeks on risk factors for the accumulation of hepatic fat in obese youth. Methods: 38 obese children and adolescents of both sexes, between 12 and 15 years old. The obesity was attested by the percentage of body fat, which was estimated by dual-energy X-ray absorptiometry (DEXA). Additionally, the amount of fat located in the trunk (kg) was estimated too. Before and after the intervention, the youths underwent biochemical blood tests (fasting complete lipid profile [mg / dL]) and ultrasonography of the liver (right size Wolves [LD cm] and left [LE in cm]). The intervention consisted of concurrent training (strength training [30 minutes] and endurance training [30 minutes]) with three sessions per week, totaling 180 minutes a week, for ten weeks. Statistical analysis was made by the test t of Student for paired data using SPSS software (17.0) and significance statistical fixed at p <5%. Results: After the intervention, significant improvements were observed in the percentage of total fat (PRE: 45.1 ± 5.3 and POST: 41.7 ± 5.6, p = 0.001) and in the trunk region (PRE: 46, 5 ± 5.6 and POST: 42.9 ± 6.3, p = 0.001). For lipid profile, reduction in total cholesterol (PRE: 164 ± 34 and POST: 148 ± 29, p = 0.001), triglycerides (PRE: 118 ± 59 and POST: 104 ± 53, p = 0.002) and lipoproteins density (PRE: 100 ± 29 and POST: 85 ± 26, p = 0.001), but not for high-density (p = 0.981). Both the LE (PRE: 8.8 ± 1.4 and POST: 7.8 ± 1.3, p = 0.001) and LD (PRE: 13.6 ± 1.3 and POST: 12.9 ± 1, 1, p = 0.001) experienced a decrease in its proportions. Conclusion: The concurrent training was effective in combating some risk factors to the accumulation of fat in the liver, as well as in reducing fat in both lobes of the organ in young obese.
Effect of a concurrent training on risk factors for the accumulation of hepatic fat of obese adolescents
Keywords: Fatty liver; Obesity; Training; cholesterol; fat; lipoprotein; triacylglycerol; adolescent; body fat; child; cholesterol blood level; clinical article; clinical protocol; computer program; density; dual energy X ray absorptiometry; echography; endurance training; human; lipid analysis; obesity; prospective study; resistance training; risk factor; school child; trunk